„Non intelligis stultitiam tuam impudentiae copulatam”. Św. Hieronim contra Pelagiusz - Jóźwiak, Magdalena (Vox Patrum, 2018)
Reading the ancient scriptures of Christians of the first centuries, one can easily notice numerous invectives. From among the Fathers of the Church there are three who in particular deserve the title of “fathers of Christian invectives”. One of those who best can be described as such is St. Jerome of Stridonius. It should not come as a surprise, because in ancient times one did not reach only for intellectual arguments when defending their views. A logical elucidation was merely a part of argumentation. The other part, of no less importance, were arguments ad hominem, including also invectives. Verbal insults were integral part of argumentation and the lack of them would decrease the value of debate. In this article, based on St. Jerome’s of Stridonius writings, I portrayed his reactions to the phenomenon of pelagianism, as well as to the person of Pelagius himself. This subject has been analysed in many articles, but I presented it from a different angle. Namely, I emphasized varied interesting invectives that St. Jerome – well-known for his sharp tongue – directed to Pelagius, basing on argumentum ad personam.